A biocompatible catalytic benzyl decaging enables activation of salicylic acid-dependent defense responses in plants - Yanhao Hu; Bo He; Mian Wei; Zhengxi Xiong; Yalin Mu; Ping Chen; Wang Chen; Jiahao Wang; Wei Yan; Yonghao Ye (Chemical Engineering Journal, 2026)

Berberine alleviated contrast-induced acute kidney injury by mitophagy-mediated NLRP3 inflammasome inactivation in a mice model - Yalin Yang; Shuang Jiang; Yu Mu; Chilu Liu; Yanxing Han; Jiandong Jiang; Yuhong Wang (Toxicology and Applied Pharmacology, 2024)

Separation of rhenium(VII) from nuclear wastewater using N-methyl-glucosamine functionalized exchange resin - Wanjun Mu; Ning Wang; Yalin Huang; Hongyuan Wei (Journal of Water Process Engineering, 2024)

Contrasting the Pb (II) and Cd (II) tolerance of Enterobacter sp. via its cellular stress responses - Zhongquan Jiang; Liu Jiang; Lin Zhang; Mu Su; Da Tian; Tong Wang; Yalin Sun; Ying Nong; Shuijin Hu; Shimei Wang; Zhen Li (Environmental Microbiology, 2020)
Summary Successful application of microorganisms to heavy metal remediation depends on their resistance to toxic metals. This study contrasted the differences of tolerant mechanisms between Pb 2+ and Cd 2+ in Enterobacter sp. Microbial respiration and production of formic acid showed that Enterobacter sp. had a higher tolerant concentration of Pb (>1000 mg l −1 ) than Cd (about 200 mg l −1 ). Additionally, SEM confirmed that most of Pb and Cd nanoparticles (NPs) were adsorbed onto cell membrane. The Cd stress, even at low concentration (50 mg l −1 ), significantly enlarged the sizes of cells. The cellular size raised from 0.4 × 1.0 to 0.9 × 1.6 μm on average, inducing a platelet‐like shape. In contrast, Pb cations did not stimulate such enlargement even up to 1000 mg l −1 . Moreover, Cd NPs were adsorbed homogeneously by almost all the bacterial cells under TEM. However, only a few cells work as ‘hot spots’ on the sorption of Pb NPs. The heterogeneous sorption might result from a ‘self‐sacrifice’ mechanism, i.e., some cells at a special life stage contributed mostly to Pb sorption. This mechanism, together with the lower mobility of Pb cations, caused higher microbial tolerance and removal efficiency towards Pb 2+ . This study sheds evident contrasts of bacterial resistance to the two most common heavy metals.